2007
DOI: 10.1001/archpsyc.64.3.305
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Distribution of Major Depressive Disorder in African Americans, Caribbean Blacks, and Non-Hispanic Whites

Abstract: When MDD affects African Americans and Caribbean blacks, it is usually untreated and is more severe and disabling compared with that in non-Hispanic whites. The burden of mental disorders, especially depressive disorders, may be higher among US blacks than in US whites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

66
925
17
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,124 publications
(1,033 citation statements)
references
References 39 publications
66
925
17
4
Order By: Relevance
“…Racial disparities exist for depressive symptom severity, recognition, and treatment15, 44, 45 and CVD outcomes 46. Nevertheless, we found that race did not appear to moderate the association between depressive symptoms and CVD.…”
Section: Discussionmentioning
confidence: 51%
“…Racial disparities exist for depressive symptom severity, recognition, and treatment15, 44, 45 and CVD outcomes 46. Nevertheless, we found that race did not appear to moderate the association between depressive symptoms and CVD.…”
Section: Discussionmentioning
confidence: 51%
“…This finding was less than the 12 month prevalence rate of 13.1% for African American women and 19.5% for non-Hispanic White women in the National Survey of American Life (Williams et al, 2007). Some researchers have noted that African American women often present to healthcare providers with somatic symptoms of depression unlike…”
Section: Typology Of Familiesmentioning
confidence: 73%
“…Caucasian women who present with melancholy which may lead to an under diagnosis of depression in African American women (Bailey, Blackman, & Stevens, 2009;Mezuk et al, 2010;Williams et al, 2007).…”
Section: Typology Of Familiesmentioning
confidence: 99%
“…However, African Americans have poorer mental health outcomes than Whites have (Williams, 2006), drop out of treatment and use emergency department services more, enter mental health treatment at a more advanced stage of mental illness, and received misdiagnoses more often than Whites with severe and persistent mental disorders (Breslau, Kendler, Su, Gaxiola-Aguilar, & Kessler, 2005;Martin et al, 2010;Nelson, 2006;Westermeyer & Janca, 1997;Williams et al, 2007).…”
Section: Mental Healthmentioning
confidence: 99%